An assessment of private equity as an alternative financing option for private companies in Zimbabwe - Machiridza, Shingai Karren (Midlands State University, 2018)
The twin effect of persistent liquidity challenges and a very low deposit base for most banks has constrained the traditional sources of finance for businesses making alternative financing sources an imperative for business continuity. Private equity is a growing alternative asset class among the developed markets and since the global financial crisis of 2008 private equity investments have shifted their focus to include emerging and frontier markets in different geographical markets. The study was therefore conducted to assess the extent to which private equity financing addresses the funding gap among private companies in different economic sectors as well as to document the awareness levels of private companies and the feasibility of private equity as an alternative source of capital. The study also sought to determine the perceptions towards private equity among private companies. The scope of the study also encompassed an analysis of the extent of the existing private equity investments in Zimbabwe in terms of the quantum among other things. A qualitative descriptive design was employed to meet the objectives of the research. Open-ended questionnaires and in-depth interviews were utilized in this research covering a total of 68 respondents. The respondents comprised of individuals from private equity/venture capital firms, asset managers and key individuals of private companies in different economic sectors mainly agriculture, mining, information communications and technology and banking and financial services. Some of the major themes from the findings were indicative that private companies‘ capital requirements were not being met by their current sources and there is limited knowledge on alternative financing options such as private equity. The study also revealed that private equity investments in Zimbabwe remain dominated by a few key players who are both local and foreign. The findings highlight the need for the establishment of an umbrella institution that represents the interests of private equity firms as an emerging group of financiers in Zimbabwe. Increased sensitization towards alternative financing options such as private equity among financial market participants is necessary to boost awareness levels and to improve perceptions.